Immature stages of Calycopis caulonia (Hewitson, 1877) (Lepidoptera, Lycaenidae, Theclinae, Eumaeini), with notes on rearing detritivorous hairstreaks on artificial diet - Duarte, Marcelo; Robbins, Robert K.; Mielke, Olaf H.h. (Zootaxa, 2005)
Details of egg, larval, and pupal morphology are described and illustrated for Calycopis caulonia (Hewitson). In particular, larval chaetotaxy is documented for the first time in Calycopis. Lab methods for inducing wild-caught Calycopis females to lay eggs and for rearing larvae on artificial diet are reported. These methods may be useful in several ways in resolving the basic taxonomy of Calycopis. Evidence concerning detritivory and myrmecophily in C. caulonia is discussed.